Improving ice plant efficiency with Al2O3 nanoparticles and evaporative cooling techniques - Nitin S. Aher; Umesh Gurnani; Laxmikant S. Dhamande; Rakhi Bornare; Anurag Hamilton (International Journal of Air-Conditioning and Refrigeration)
Abstract This study focuses on reducing energy consumption in vapor compression refrigeration-based ice plants by incorporating nanoparticle in secondary refrigerants and evaporative cooling technique. Experimental evaluations were performed on a test rig using brine and ethylene glycol as secondary refrigerants. Results showed that brine outperformed glycol, reducing ice formation time by 15% when combined with evaporative cooling. Further enhancement was achieved by incorporating Al2O3 nanoparticles into the brine, which, combined with direct evaporative cooling, reduced ice formation time by 20% compared to glycol. The improved system demonstrated significant performance gains, lowering energy costs and enhancing the Coefficient of Performance (COP).